Left atrial enlargement and right ventricular hypertrophy in essential hypertension. (April 2014) - Cuspidi, Cesare; Negri, Francesca; Tadic, Marijana V.; Sala, Carla; Parati, Gianfranco
Abstract Aim. Diastolic dysfunction related to hypertensive left ventricular hypertrophy (LVH) has been shown to affect right-sided cardiac morphology and haemodynamics. As left atrial enlargement (LAE) is a marker of chronically elevated left ventricular (LV) filling pressure and diastolic dysfunction, we investigated the relationship between LAE and right ventricular hypertrophy (RVH) in systemic hypertension. Methods. A total of 330 essential hypertensives, categorized according to tertiles of left atrial (LA) diameter indexed to body surface area were considered for the analysis. All subjects underwent a quantitative echocardiographic examination as well as extensive clinical and laboratory investigations. RVH was defined as anterior right ventricular (RV) wall thickness ≥ 6.0/5.5 mm in men and women, respectively, and LVH as LV mass index ≥ 51/47 g/m2.7 in men and women, respectively. Results. The prevalence of LVH increased across LA diameter tertiles from 21.0% to 50% and that of RVH from 26.3% to 41.8% (p < 0.01for both). This was also the case for biventricular hypertrophy (from 10.0% to 26.0%, p < 0.01). Differences in both LV and RV structure across LA diameter tertiles remained significant after adjusting for age, office systolic/diastolic blood pressure and duration of hypertension. Similar results were obtained when study population was divided according to absolute LA diameter tertiles. Conclusions. Our findings provide further evidence of an interaction between left and right chambers in systemic hypertension by showing that LAE is associated with RVH. The clinical and prognostic implications of such observation remain be evaluated in future prospective studies.